Improving Utilization of the Chemotherapy Unit through Implementing the Medication Early Release Project - Mohsen Alzahrani; Mohammad Alkaiyat; Mona Alshami; Thamer Alotaibi; Sultan Meashi; Elham Al Enizi; Hussam Shehata; Ammar Khaleel; Anas Abu Esbaa; Reem Al Harbi; Mohamad Alharbi (Global Journal on Quality and Safety in Healthcare, 2023)
Introduction The outpatient oncology infusion unit is very busy, serving 60 to 70 patients per day. Due to a limited number of nurses, treatment chairs, only one pharmacy hood for bio-hazardous drug preparation, and other factors, patients wait a long time before starting their treatment, which affects the patient experience negatively. We conducted a quality improvement project to reduce the waiting time before starting the treatment, improve the patients' experience, and allow the unit to work more effectively through better resource utilization and accommodating more patients. Methods A committee was formed with representatives from oncology nursing and the quality specialist, chemotherapy pharmacy supervisor, data manager, and a medical consultant (team leader). We studied baseline data of patient waiting times from January to March 2019 and the factors that contributed to delays before starting the treatment. The charge nurse identified patients who could safely have their medication released early in the morning at 7 am, enabling the pharmacy to dispense at 8 am without their actual presence being required in the infusion suite (i.e., medication early release program or MERP). Multiple plan-do-study-act (PDSA) cycles were implemented to achieve a wait time from check-in to medication administration of less than 60 minutes. Data collected included check-in time, chair time, vital signs time, administration time, and discharge time. Additionally, reasons for drug wastage were assessed for patients who did not receive the prepared medication. A patient satisfaction survey was conducted with the patients before and after being enrolled in the program. Results At baseline, average waiting time for patients receiving similar medications in the MERP was 2 hours and 27 minutes. After the first intervention, average waiting time was reduced to 1 hour and 24 minutes, and small improvements were observed after each PDSA cycl. A major breakthrough occurred after an intensive patient education program and enforcement of strict compliance with the criteria in selecting the patients appropriate for theMERP. Average waiting time wasreduced to ≤ 60 minutes, and in November 2022, it was 30 minutes on average. Drug wastage was identified as a balancing measure. We were successful in reducing drug wastage by implementing several changes and patient education measures and achieved zero wastage. The patient satisfaction survey showed better satisfaction with the new changes. Conclusion A positive impact was achieved in this quality improvement project, with a significant reduction in the average waiting time for patients to start receiving chemotherapy. The outcome of this project has been maintained for 4 years and is still ongoing.